2014
DOI: 10.1371/journal.pone.0084021
|View full text |Cite
|
Sign up to set email alerts
|

Mating Behaviour in Laevicaudatan Clam Shrimp (Crustacea, Branchiopoda) and Functional Morphology of Male Claspers in a Phylogenetic Context: A Video-Based Analysis

Abstract: Clam shrimps are freshwater branchiopod crustaceans which often present complicated breeding systems including asexual reproduction (parthenogenesis) and mixed mating systems (in androdioecious species both selfing and outcrossing occurs due to the co-presence of hermaphrodites and males). Reproductive patterns of Spinicaudata, which contains most clam shrimp species, have received much attention. Another group of clam shrimps, Laevicaudata, which holds a key position in branchiopod phylogeny, has practically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 38 publications
(82 reference statements)
2
34
1
Order By: Relevance
“…). The function of the different parts of the clasper has been studied in detail for a laevicaudatan by Sigvardt and Olesen (). No such studies are available for spinicaudatans or cyclestheridans, but it has been suggested that stout spines on the tip of the movable finger in some spinicaudatans play a role in mate recognition (Schwentner et al, ).…”
mentioning
confidence: 99%
“…). The function of the different parts of the clasper has been studied in detail for a laevicaudatan by Sigvardt and Olesen (). No such studies are available for spinicaudatans or cyclestheridans, but it has been suggested that stout spines on the tip of the movable finger in some spinicaudatans play a role in mate recognition (Schwentner et al, ).…”
mentioning
confidence: 99%
“… “Type 2 thrusting” after Weeks et al () and Weeks and Benvenuto (), “brushing movements” after Sigvardt and Olesen (). Male succeeds in getting its hind body in contact with the female hind body.…”
Section: Resultsmentioning
confidence: 99%
“…10 pairs, first pair modified as claspers. Right and left claspers equal in size and shape, of typical Lynceus form (clasper terminology follows Sigvardt &Kaji et al 2014). Endite 1 of clasper limb typical for genus, lobiform, margined with short setae.…”
Section: Etymologymentioning
confidence: 99%
“…Endite 3 broad, oval, laterally compressed, with proximal anterior margin bearing patch of fine plumose setae. Median margin or "palm" region ("gripping area") of clasper with slender, relatively short setae (~100 μm) bearing sparse lateral setulae (type 3 or 4 setae of Sigvardt & Olesen 2014), positioned in semicircular arrangement leaving glabrous area under endopod apex. Anterior margin of glabrous area partially obscured by endopod, with short row of 4 cylindrical peglike spines (type 2 setae of Sigvardt & Olesen 2014).…”
Section: Etymologymentioning
confidence: 99%
See 1 more Smart Citation